Modelling and performance evaluation of a three-phase capacitive voltage sensor topology - Van der Merwe, S. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.